Oppression Reflected In Charles Dickens' Oliver Twist Novel (1837): A Sociological Approach - Jumiati, Sri, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem in this research is to reveal the existance of oppression in England as reflected in Charles Dickens' Oliver Twist Novel. The research analyses Charles Dickens' Oliver Twist novel in a term of structural elements and analysis the England society during industrial revolution in the late of nineteenth century based on sociological perspective. In analysing the novel, the reseacher uses qualitative method. The data are divided into two kinds data, namely primary data and secondary data. The primary data sources is the novel entitled Oliver Twist by Charles Dickens which is published in 1873. And the secondary data is the sources which is related to the issue taken by reseacher, such as the book of the theory namely sociological approach and other resources about England society during industrial revolution in the late of ninetenth century.The method of getting data is library research. However the descriptive analysis is the technique of data analysis. The outcome of the study draws the following conclusions. Firstly, based on the structural analysis of the novel, it is created based on the social phenomena in England during industrial revolution in the late ninetenth century. Secondly, Charles Dickens critizes the social condition inside the country which reveal the social injustice such as oppression which is divided into five parts, namely exploitation, marginalization, powerlessness, cultural imperialism and the last is violence. It also reveals the needs of goverment to create justice in order to create peace and save childern.